2009
DOI: 10.1007/s00216-009-2688-x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evaluation of a compact magnetically boosted radiofrequency glow discharge for time-of-flight mass spectrometry

Abstract: A compact magnetically boosted radiofrequency glow discharge (GD) has been designed, constructed and its analytical potential evaluated by its coupling to a mass spectrometer (MS). Simple modifications to the original source configuration permitted the insertion of permanent magnets. Small cylindrical Nd-Fe-B magnets (diameter = 4 mm, h = 10 mm) were placed in an in-house-modified GD holder disc that allows easy and fast exchange of the magnets. The different processes taking place within the GD plasma under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In such a process, electrons and cations in the plasma are oscillated between the sample surface and the counter electrode . In a continuous sputtering process, a negative self-bias could be formed on the sample, since the electrons in the plasma are more mobile than the positive charged ions. , In a rf-GD process, such negative self-bias formed on the sample surface could increase sputtering rate and ionization efficiency. , For a mass spectrometry, the sputtering rate and ionization efficiency play important roles in achieving the optimum analytical performance, which could also be influenced by other factors such as gas pressure, rf-power, sample thickness, lattice binding energy of sample and so on. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In such a process, electrons and cations in the plasma are oscillated between the sample surface and the counter electrode . In a continuous sputtering process, a negative self-bias could be formed on the sample, since the electrons in the plasma are more mobile than the positive charged ions. , In a rf-GD process, such negative self-bias formed on the sample surface could increase sputtering rate and ionization efficiency. , For a mass spectrometry, the sputtering rate and ionization efficiency play important roles in achieving the optimum analytical performance, which could also be influenced by other factors such as gas pressure, rf-power, sample thickness, lattice binding energy of sample and so on. , …”
mentioning
confidence: 99%
“…However, the generator power is usually coupled capacitive to the plasma, so that the plasma power decreases with increasing thickness, thus sputtering rates, sensitivities and signal intensity decrease at the same time . In recent years, some efforts have been made to improve the ionization efficiency and detection sensitivity in GD-MS by utilization of power pulse or adding external magnetic field . The benefits of the external magnetic field, classified as magnetron, have been successfully exploited in a variety of spectroscopies. , For instance, Vega et al introduced a permanent block magnet into the rf-GD chamber coupled with an optical emission spectroscopy .…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] Additionally, several methodological strategies, such as use of plasma gas mixtures, deposition of conductive thin layers, or magnetically boosted glow discharges, have been investigated using rf-GD spectroscopy to further enhance the analytical capabilities of this technique. [11][12][13][14][15] Particularly, in magnetically boosted GD, the combination of an external magnetic field and the electric field, applied between the anode and the cathode, causes modifications in the charged particle motion within the GD plasma. At the relatively low magnetic fields employed in glow discharge spectroscopy, only electron trajectories are significantly affected as ions are much heavier and their paths more difficult to alter.…”
Section: Introductionmentioning
confidence: 99%
“…Glow discharge (GD) coupled to optical emission spectrometry (OES) is considered to be a useful technique for the direct bulk, surface and in-depth profile analysis of solid materials, both for homogeneous and coated samples. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Nowadays, the continuous evolution in the field of high performance materials is giving rise to new challenges in the application field of GD-based techniques. Therefore, today radiofrequency (RF) GD-OES is of great analytical interest as it is applicable to conductors, 3 semiconductors 4 and non-conductors, [5][6][7][8] which is probably its main advantage as compared with the better-known direct current (dc) GD counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…This is an attractive option to enhance the analytical capabilities of GD as it provides the possibility of improved sputtering rates, as well as higher excitation and ionisation efficiencies. Studies, where the magnetic field (using Co-Sm magnets or Nd-Fe-B magnets) was located behind the sample, [15][16][17][18] embedded 19 inside the anode or placed around the anode, 20 have been carried out previously, some of them with GD Grimm type sources 16,18,20 combined with optical or mass spectrometry. It has also been shown that the observed enhancement of the corresponding analyte ion/emission intensities were dependant upon the GD discharge operating conditions.…”
Section: Introductionmentioning
confidence: 99%